Glutamine synthetase isoforms in nitrogen‐fixing soybean nodules: Distinct oligomeric structures and thiol‐based regulation. Issue 2 (10th December 2014) - Masalkar, Pintu D.; Roberts, Daniel M.
Abstract : Legume root nodule glutamine synthetase (GS) catalyzes the assimilation of ammonia produced by nitrogen fixation. Two GS isoform subtypes (GS1 β and GS1 γ) are present in soybean nodules. GS1 γ isoforms differ from GS1 β isoforms in terms of their susceptibility to reversible inhibition by intersubunit disulfide bond formation between C159 and C92 at the shared active site at subunit interfaces. Although nodule GS enzymes share 86% amino acid sequence identity, analytical ultracentrifugation experiments showed that GS1 γ is a dodecamer, whereas the GS1 β is a decamer. It is proposed that this difference contributes to the differential thiol sensitivity of each isoform, and that GS1 γ1 may be a target of thiol‐based regulation. Abstract : Soybean nodule glutamine synthetase isoforms show distinct sensitivity to redox agents. The GS1 γ isoform is reversibly inhibited by intermolecular disulfide bond formation. The disulfide bond spans the active site interface between GS subunits. GS1 γ forms a unique dodecameric structure compared to other plant GS1 enzymes. GS1 γ may be a target for thiol‐based regulation in nitrogen fixing nodules.